Configuration analysis on servitisation transformation of sporting goods manufacturing enterprises: The case study of 33 listed companies of China - Yunfei Hu; Laibing Lu; Qiuying Li (PLoS ONE, 2025)
This study explores the multifactorial and complex causal relationships affecting the performance of sporting goods manufacturing enterprises during service transformation. A fuzzy set qualitative comparative analysis method was applied using 33 sporting goods manufacturing enterprises listed on the Shanghai and Shenzhen A-shares and the New Third Board in China. The study developed a model using the Technology-Organization-Environment(TOE) theoretical framework, to analyse the factors driving the servitisation transformation of China’s sporting goods manufacturers. The results revealed that (1) none of the seven secondary factors such as the degree of digital transformation, innovation capability, top management level, staff knowledge structure, organisational redundancy, government support, and degree of marketization individually contribute to enhancing the servitisation performance of sporting goods manufacturing enterprises in China. (2) The four grouping paths that drive the transformation of the servitisation of sporting goods manufacturing enterprises in China are divided into three types: “talent–resource driven”, “technology–organisation driven, and “technology–talent driven”. This study reveals the role of multiple factors behind the transformation of servitisation and the upgrading of sporting goods manufacturing enterprises and provides useful insights into the structural rationalisation and advanced development of China’s sports industry.